2019
DOI: 10.1002/asi.24322
|View full text |Cite
|
Sign up to set email alerts
|

A joint neural network model for combining heterogeneous user data sources: An example of at‐risk student prediction

Abstract: Information service providers often require evidence from multiple, heterogeneous information sources to better characterize users and offer personalized service. In many cases, statistic information (for example, users' profiles) and sequentially dynamic information (for example, logs of interaction with information systems) are two prominent sources that can be combined to achieve optimized results. Previous attempts in combining these two sources mainly exploited models designed for either static or sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This approach employed a neural network structure to keep track of the trends of students' attrition. Similarly, Qiao and Hu (2020) implemented a joint neural network model to analyze both user demographic information and learning behaviors for predicting at-risk students. The experimental results demonstrated the proposed model outperformed the commonly used baseline models in identifying at-risk students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach employed a neural network structure to keep track of the trends of students' attrition. Similarly, Qiao and Hu (2020) implemented a joint neural network model to analyze both user demographic information and learning behaviors for predicting at-risk students. The experimental results demonstrated the proposed model outperformed the commonly used baseline models in identifying at-risk students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To demonstrate the validity of the proposed method, we used the OULAD (see https://analyse.kmi.open.ac.uk/open_dataset) dataset collected by Open University (Kuzilek et al., 2017). Multiple studies (Adnan et al., 2021; Aljohani et al., 2019; Hlosta et al., 2018, 2017; Qiao & Hu, 2020) have been conducted using this dataset as a baseline to verify the effectiveness of their methods in predicting student learning performance. In this study, we selected four courses purposely from the dataset, where two of them (i.e., AAA_2013J and AAA_2014J) were in the social science field and the other two (i.e., CCC_2014B and CCC_2014J) were in the STEM field.…”
Section: Dataset Description and Feature Preparationmentioning
confidence: 99%
“…However, this study has important limitations, like the fact of analyzing only two courses of a total of seven available. The other studies that use assignment information, a 30% of works, use this factor together with the rest of sources sources [3,39,[41][42][43]. Thus, the real relevance of this factor in the final prediction cannot be analyzed.…”
Section: Predicting Student Success In Distance Higher Educationmentioning
confidence: 99%
“…Regarding the purpose of the different works, under the main task of predicting student performance, it can be found that the majority of studies pretend to predict whether the student will pass or fail a course [3,27,[30][31][32][37][38][39][40][41][42][43][44][45]. Other approaches focus on the dropout rate [26,29,32,33], while others follow an early prediction study [33,35,36,46].…”
Section: Predicting Student Success In Distance Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation